AB0149 Decreased microrna-130a expression drives activation of classical dendritic cells from patients with primary sjögren's syndrome. (12th June 2018) - Lopes, A.P.; van Roon, J.A.; Blokland, S.L.; Wang, M.; Chouri, E.; Kruize, A.A.; Burgering, B.M.; Rossato, M.; Radstake, T.R.; Hillen, M.R.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease characterized by lymphocytic infiltration of the exocrine glands and dryness of mouth and eyes. Classical dendritic cells are very potent antigen presenting cells known to induce strong T-cell proliferation and cytokine production. Objectives: Considering the critical role of microRNAs (miRNAs) in regulation of gene expression, we investigated miRNA expression in circulating CD1c + dendritic cells (cDCs) of patients with pSS. Methods: Two independent cohorts consisting of pSS patients and healthy controls were established: a discovery cohort (15 pSS, 6 HC) was used to screen the expression of a large panel of 758 miRNAs. An independent validation cohort (14 pSS, 11 HC) was used to test the reproducibility of the results. cDCs were isolated from peripheral blood using MACS and miRNA profiling of 758 targets was performed using the OpenArray platform in the discovery cohort. A selection of 16 differentially expressed miRNAs was measured in the validation cohort using a custom-made array. Isolated cDCs from HC were stimulated with a panel of Toll-like receptor (TLR) ligands and the expression of miR-130a and miR-708 was measured by qPCR. The effect of transfection with miR-130a on protein synthesis was analysed by using the pulsed stable isotope labelling by amino acids in cell culture (pSILAC) method (quantitative mass spectrometry-based technique) in a HEK-293T cell-line. Results: A total of 24 miRNAs was downregulated in pSS patients versus HC in the discovery cohort (p<0.05, with a difference between the groups of >log2). Of the 16 miRNAs that were selected for replication, the decreased expression of miR-130a and miR-708 in pSS was validated. Activation of cDCs via TLR3 and TLR7/8 induced downregulation of both miRNA-130a and miRNA-708. Transfection with a miR-130a mimic resulted in downregulation of several proteins with a seed match for the miRNA. These proteins are known to be involved in membrane trafficking and cell activation trough CREB/NF-kB signalling. Conclusions: miR-130a and miR-708 are significantly downregulated in cDCs of patients with pSS. We show that the expression of these miRNAs is decreased upon cDC activation and that upregulation of miR-130a decreases the expression of proteins involved in the CREB/NF-kB pathway. As such, these miRNAs seem to be involved in cDC activation and reflect enhanced activation of circulating cDCs from pSS patients. Disclosure of Interest: None declared